Analisis Gaya Belajar Siswa pada Mata Pelajaran IPS di Kelas VII SMP Negeri 9 Kota Jambi - Diliza Afrila; Abd Rahman (Universitas Batanghari Jambi, 2019)
This study aims to analyze the learning styles of students on the subjects of social studies in class VII SMP Negeri 9 Kota Jambi. The type of this research is descriptive research with quantitative approach. The population in this study is 251 people. Sampling technique in this research is proportional random sampling, so selected 72 students as sample of research. Data collection techniques in this study is to spread the questionnaire to the research respondents. Data analysis technique in this research is descriptive analysis. The results showed that the average of student learning style variables on social studies subjects in class VII of SMP Negeri 9 Kota Jambi is 4.15 with Respondent Achievement Level (TCR) of 82.93. This suggests that learning style variables fall into either category. From 3 (three) indicator of studied learning style, it is known that (1) visual indicator get average, that is 4,22 with TCR equal to 84,47, so that in good category, (2) kinesthetic indicator get average 4 , 18 with TCR of 83.58, so it is in good category, and (3) the auditorial indicator obtains the average, that is 4.04 with TCR of 80.74, so it is in good category.